EXTH-57. EFFICACY OF SOLUBLE PANOBINOSTAT (MTX110) IN PRECLINICAL MODELS OF ADULT GLIOBLASTOMA. (12th November 2021) - Palmer, Greg; Keir, Stephen T; Ashley, David M; Davies, Rhian; Williams, Ben; Rees, Zoe; Laemont, Keith; Belloni, Rafaela; Damment, Stephen J P; Conlon, Kelly
Abstract: INTRODUCTION: One of the biggest challenges in treating glioblastoma is achieving effective local drug concentrations, and trials using systemic administration of therapeutics have failed in GBM despite compelling pre-clinical evidence. MTX110 (Midatech Pharma PLC) is a water-soluble form of panobinostat currently in clinical development for DIPG and medulloblastoma using direct tumor delivery. We have previously reported a significant positive benefit of MTX110 in a subcutaneous GBM mouse model in an IDH1 mutated cell line. Here we present follow on data on the potential for MTX110 synergy with radiation in pre-clinical in vivo models. We also present data on efficacy of MTX110 in a panel of GBM cell lines. METHODS: In vitro: Cell lines were incubated with MTX110 for 72h over a range of concentrations (1nM-10µM). Each concentration was tested in triplicate with the appropriate blank controls included in each plate. After 72 hours, cell viability was measured via luminescence signal (Promega CellTiter-Glo Luminescent Cell Viability Assay kit (Promega-G7573) read via 2104 EnVision Multilabel Reader, PerkinElmer. In vivo: Tumor-bearing mice were stratified to either the vehicle control or treatment group based on median tumor volume and were treated with MTX110 at a dose of 15mg/kg IP, 5 days consecutively for 2 consecutive weeks, following radiation treatment at a dose of 4Gy delivered as a single fraction on day 1. RESULTS: In vitro, MTX110 demonstrated cytotoxic activity in 4 GBM cell lines (U87MG, U251MG, U118MG and T98G) with an average IC50 value in the region of 40nM (17-43nM). In vivo MTX110 in combination with radiation treatment showed an enhanced delay in tumor growth of approximately 50% compared to MTX110 or radiation alone. The results are supportive of the planned exploratory trial in GBM with MTX110.